Preparation method and application of metal-doped lanthanum oxide catalyst
By doping lanthanum oxide and non-lanthanum metal salts into the catalyst and treating them with ionic liquids, a catalyst for urea alcoholylation reaction was prepared, which solved the problems of low catalytic activity and complex preparation, and achieved high efficiency and high selectivity Glyceride preparation and easy separation of catalysts.
Patent Information
- Application Number
- CN202411428504.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-14
AI Technical Summary
The existing catalysts have problems such as low catalytic activity, complex preparation process, and difficulty in separation when catalyzing the synthesis of glycerol carbonate by urea and glycerol, and the efficiency of heterogeneous catalysts is low.
Using metal-doped lanthanum oxide catalyst, iron-doped lanthanum oxide catalyst is prepared by mixing with lanthanum nitrate hexahydrate and non-lanthanum metal salts in anhydrous methanol, adding ionic liquid, and rotary evaporating and drying, and under mild conditions It is used for urea alcoholylation reaction.
The efficient conversion of catalytic urea and glycerol is achieved. The yield of glycerol carbonate is higher than 90%, the selectivity can reach 99.99%, and the catalyst is easy to separate and recover, the preparation process is simple and the performance is stable.
Smart Images

Figure BDA0005082886530000041 
Figure BDA0005082886530000051 
Figure BDA0005082886530000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst synthesis, and in particular to a preparation method and application of a metal-doped lanthanum oxide catalyst for catalyzing the synthesis of glycerol carbonate from urea and glycerol. Background Art
[0002] Glycerol is a byproduct produced during the production of biodiesel and is considered a renewable and clean diesel fuel. The increase in biodiesel production has led to an excess of glycerol, making it a promising platform compound and an important component of future biorefining. Among the chemicals derived from glycerol, glycerol carbonate (GC) is a high-value-added product with great potential for application. It has good biodegradability, low toxicity, high boiling point and environmental friendliness. It is widely used as an important component of biosolvents, gas separation membranes, polyurethane foams, surfactants, coatings, paints and detergents.
[0003] At present, the reported process routes for preparing glycerol carbonate mainly include phosgene method, carbonylation method, transesterification method, urea alcoholysis method, etc. Among them, the alcoholysis reaction with glycerol and urea as raw materials has a simple process flow and can achieve efficient conversion of glycerol under relatively mild conditions with high yield and good selectivity. The reactant urea is cheap and easy to obtain, and the by-product ammonia produced during the alcoholysis reaction can be recycled as a raw material for synthesizing urea, thus realizing green and recyclable chemical production.
[0004] The design and development of high-activity and high-stability catalytic systems has become a research focus for the preparation of glycerol carbonate by urea alcoholysis. At present, metal salts, metal oxides, supported catalysts, ionic liquids, etc. are mostly studied for catalyzing urea alcoholysis reactions. Patent (CN 117339619 A) discloses a palladium-loaded Cu-ZIF catalyst for catalyzing the alcoholysis of urea and glycerol to prepare glycerol carbonate GC. During the preparation process, the copper-doped ZIF-8 carrier is first synthesized, and then Zn is removed by calcination to obtain a copper-doped nitrogen-carbon material (Cu-NC), and finally palladium is loaded to obtain a Pd / Cu-ZIF catalyst. The yield and selectivity of GC obtained by the catalysis are 24.50% and 56.58%. Patent (CN 114957009 B) provides a solid nitrogen-containing nanocarbon catalyst prepared by a sol-gel method, which catalyzes the reaction of urea and glycerol at 105-125°C for 6-8h, and the yield of GC obtained is 62.9%-93.2%, but the preparation of the catalyst is relatively cumbersome. Patent (CN 103357394 B) reports a binary metal oxide catalyst that catalyzes the alcoholysis of urea to synthesize GC. The catalyst with appropriate acidic and basic sites has a glycerol to urea molar ratio of 1:2 to 2:1, a catalyst dosage of 3% to 7% of the mass of glycerol, a reaction temperature of 120 to 160°C, a reaction pressure of 2 to 6 kPa, and a reaction time of 3 to 7 hours. The conversion rate of glycerol obtained by catalysis is 80% to 85%, and the yield of GC is 73% to 83%. Literature (Korean Journal of Chemical Engineering, 2014, 31, 972-980) uses a supported ZnBr2-containing ionic liquid catalyst (PS-(Im)2ZnBr2) to study the reaction system of urea and glycerol alcoholysis to prepare glycerol carbonate. The reaction was carried out at 140°C and 14.7 kPa for 6 hours, and the yield of GC was 47.6%, the selectivity was 72.3%, and the activity of the catalyst decreased significantly after being used 4 times. The literature (Catalysis Science & Technology, 2024, 14, 145-152) prepared a finely dispersed Pd / Cu-NC catalyst by impregnation. By doping with metallic copper, the reaction was carried out at 140°C and 4MPa for 1.5h, and the yield and selectivity of GC obtained by catalysis can reach 91.1% and 93.4%. However, the preparation of the catalyst requires the preparation of the Cu-NC carrier by hydrothermal method and high-temperature calcination, and then the Pd / Cu-NC is formed by impregnation, and the preparation conditions are relatively harsh.
[0005] Therefore, in order to address the problems of difficulty in separating homogeneous catalytic systems and low catalytic efficiency and complex preparation process of heterogeneous catalysts, it is necessary to develop a catalyst that is simple to prepare, has high catalytic activity, good stability, is environmentally friendly and easy to separate and recover, so as to achieve efficient preparation of glycerol carbonate under relatively mild conditions. Summary of the invention
[0006] The present invention provides a method for preparing a metal-doped lanthanum oxide catalyst and an application of the catalyst in catalyzing alcoholysis of urea to prepare glycerol carbonate. The catalyst has mild preparation conditions, excellent catalytic performance and is easy to separate from the reaction system, thus solving the problems of low catalytic activity and harsh preparation process of existing catalysts.
[0007] To solve the above problems, the specific technical solution of the present invention is as follows:
[0008] The present invention provides a method for preparing a metal-doped lanthanum oxide catalyst, the preparation method comprising the following steps:
[0009] (1) weighing a certain ratio of lanthanum nitrate hexahydrate and non-lanthanum metal salt, adding them to anhydrous methanol, stirring them fully, waiting for them to dissolve, and then drying them in a vacuum drying oven at 60° C. to obtain a precursor;
[0010] (2) Weigh an appropriate amount of anhydrous methanol and add it to the round-bottom flask containing the precursor, stir thoroughly until the precursor is completely dispersed;
[0011] (3) Slowly add the ionic liquid into the round-bottom flask, and after it is dissolved, place it at 55°C for rotary evaporation. The obtained sample is centrifuged and washed multiple times in anhydrous ethanol, and finally transferred to a 60°C vacuum drying oven for drying.
[0012] The above-mentioned method for preparing a metal-doped lanthanum oxide catalyst, the metal element in the non-lanthanum metal salt in step (1) is any one of zinc, magnesium, aluminum, copper, iron, manganese, cobalt, nickel, calcium, zirconium and cerium, preferably any one of zinc nitrate, magnesium nitrate, aluminum nitrate, copper nitrate, ferric nitrate, ferrous nitrate, manganese nitrate, cobalt nitrate, nickel nitrate, calcium nitrate, zirconium nitrate, cerium nitrate, zinc halide, magnesium halide, aluminum halide, copper halide, ferric halide, ferrous halide, manganese halide, cobalt halide, nickel halide, calcium halide, zirconium halide, cerium halide, zinc sulfate, magnesium sulfate, copper sulfate, cuprous sulfate, ferrous sulfate, ferrous sulfate, manganese sulfate, cobalt sulfate, nickel sulfate, calcium sulfate, zirconium sulfate and cerium sulfate.
[0013] In the above-mentioned method for preparing a metal-doped lanthanum oxide catalyst, the molar ratio of the lanthanum element in the lanthanum nitrate hexahydrate to the non-lanthanum metal element in the non-lanthanum metal salt in step (1) is 1:(0.01-0.5), preferably 1:0.1.
[0014] In the above-mentioned method for preparing a metal-doped lanthanum oxide catalyst, the ionic liquid in step (3) is any one of an imidazole salt, a quaternary phosphonium salt and a quaternary ammonium salt ionic liquid, and its structure is shown in the following formulas I, II and III:
[0015]
[0016] Wherein, in the ionic liquid structure, R1, R2, R3, and R4 are any one of C1-C8 alkyl groups; the anion X - It is any one of a halogen ion, a hydroxide ion, a tetrafluoroborate ion, a hexafluorophosphate ion, a carboxylate ion, and an imidate ion. The anion is preferably a halogen ion or a hydroxide ion, and more preferably a hydroxide ion.
[0017] The present invention also provides an application method of using the metal-doped lanthanum oxide catalyst prepared above to catalyze the alcoholysis of urea to synthesize glycerol carbonate, wherein the general reaction formula of the alcoholysis of urea to synthesize glycerol carbonate is as follows:
[0018]
[0019] Wherein, the specific steps of synthesizing glyceryl carbonate are:
[0020] (1) Urea and glycerol in a certain molar ratio are added to a 25 mL round-bottom flask. The round-bottom flask is connected in sequence to a reflux condenser, an ammonia absorption device, and a vacuum pump, and is gradually heated in a constant temperature oil bath while being stirred continuously.
[0021] (2) Then, an appropriate amount of the prepared metal-doped lanthanum oxide catalyst is weighed and added to the flask, and heating is continued while turning on the vacuum pump to maintain the system pressure.
[0022] (3) After the reaction is completed, the product is cooled and the pressure in the system is restored to normal pressure; the catalyst is separated and recovered by centrifugation and washing, and the reaction product is quantitatively analyzed by gas chromatography.
[0023] The above-mentioned metal-doped lanthanum oxide catalyst is used to catalyze the alcoholysis of urea to synthesize glycerol carbonate, wherein the molar ratio of urea to glycerol is (0.1-3):1, preferably 1.5:1.
[0024] The above-mentioned metal-doped lanthanum oxide catalyst is used to catalyze the alcoholysis of urea to synthesize glycerol carbonate, and the amount of the catalyst is 1% to 10% of the mass of glycerol, preferably 5%.
[0025] The above-mentioned metal-doped lanthanum oxide catalyst is used to catalyze the alcoholysis of urea to synthesize glycerol carbonate, and the alcoholysis reaction temperature is 100°C to 180°C, preferably 140°C.
[0026] The above-mentioned metal-doped lanthanum oxide catalyst is used to catalyze the alcoholysis of urea to synthesize glycerol carbonate, and the alcoholysis reaction pressure is 5 to 50 kPa, preferably 7 kPa.
[0027] The above-mentioned metal-doped lanthanum oxide catalyst is used to catalyze the alcoholysis of urea to synthesize glycerol carbonate, and the alcoholysis reaction time is 1 to 10 hours, preferably 4 hours.
[0028] The catalyst prepared by the present invention has the following advantages:
[0029] (1) The metal-doped lanthanum oxide catalyst provided by the present invention has a simple preparation process, mild preparation conditions, high catalytic efficiency, stable performance and is easy to separate from the reaction system.
[0030] (2) The metal-doped lanthanum oxide catalyst provided by the present invention significantly improves the catalytic performance of a single lanthanum oxide catalyst by metal doping in an ionic liquid. The yield of glycerol carbonate obtained by catalyzing urea alcoholysis is higher than 90%, and the selectivity can reach 99.99%.
[0031] (3) The metal-doped lanthanum oxide catalyst provided by the present invention is used to catalyze the synthesis of glycerol carbonate. The raw material urea is cheap and easily available, is environmentally friendly, and does not require the addition of additional reaction solvents. Efficient conversion of glycerol can be achieved under relatively mild conditions. DETAILED DESCRIPTION
[0032] The preparation method and application of the metal-doped lanthanum oxide catalyst provided by the present invention are further explained in conjunction with the following specific implementations, but are not limited to the following examples.
[0033] Example 1
[0034]
[0035] Preparation of the catalyst: First, weigh 1.30 g of lanthanum nitrate hexahydrate and 0.061 g of ferric nitrate nonahydrate (the molar ratio of lanthanum to iron is 1:0.05) and add them to a 100 mL round-bottom flask containing 10 mL of anhydrous methanol, stir for 10 min, wait for it to be fully dissolved, and place it in a 60°C vacuum drying oven to dry to obtain a precursor; then, weigh 30 mL of anhydrous methanol and add it to the round-bottom flask containing the precursor, stir it fully, and wait for the precursor to be completely dispersed; slowly add 3 g of ionic liquid tetraethylammonium hydroxide to the flask, wait for it to dissolve, and perform rotary evaporation at 55°C. Finally, the obtained sample is centrifuged in anhydrous ethanol, washed 3 to 5 times, and transferred to a 60°C vacuum drying oven to dry for 24 hours to obtain an iron-doped lanthanum oxide catalyst.
[0036] The steps of preparing glycerol carbonate by alcoholysis of urea with a catalyst are as follows: 1.125g urea and 1.15g glycerol (the molar ratio of urea to glycerol is 1.5:1) are added to a 25mL round-bottom flask, and the round-bottom flask is connected in sequence with a reflux condenser, an ammonia absorption device, and a vacuum pump, etc., and gradually heated and stirred in a constant temperature oil bath. Then, 0.058g of catalyst (the amount of catalyst is 5% of the urea feed amount) is weighed and added to the flask, and the reaction is continued to be heated to 140°C, and the vacuum pump is turned on to maintain the pressure at 7kPa for 4h. After the reaction is completed, the product is cooled and the pressure in the system is restored to normal pressure; the catalyst is separated and recovered by centrifugation and washing, and the reaction product is quantitatively analyzed by gas chromatography, and the yield of glycerol carbonate is 85.97% and the selectivity is 97.46%.
[0037] Example 2
[0038] The same as in Example 1, except that the non-lanthanum metal salt used in the catalyst preparation process was 0.030 g of manganese dichloride tetrahydrate, and the other preparation steps remained unchanged. The yield of glycerol carbonate was 83.87%, and the selectivity was 97.14%.
[0039] Example 3
[0040] The same as in Example 1, except that the non-lanthanum metal salt used in the catalyst preparation process was 0.044 g of nickel nitrate hexahydrate, and the other preparation steps remained unchanged. The yield of glycerol carbonate was 83.68%, and the selectivity was 99.37%.
[0041] Example 4
[0042] The same as in Example 1, except that the non-lanthanum metal salt used in the catalyst preparation process was 0.056 g of aluminum nitrate nonahydrate, and the other preparation steps remained unchanged. The yield of glycerol carbonate was 73.54%, and the selectivity was 95.82%.
[0043] Example 5
[0044] The same as in Example 1, except that the non-lanthanum metal salt used in the catalyst preparation process was 0.065 g of cerium nitrate hexahydrate, and the other preparation steps remained unchanged. The yield of glycerol carbonate was 80.96%, and the selectivity was 97.68%.
[0045] Example 6
[0046] The same as in Example 1, except that the non-lanthanum metal salt used in the catalyst preparation process was 0.064 g of zirconium nitrate pentahydrate, and the other preparation steps remained unchanged. The yield of glycerol carbonate was 55.16%, and the selectivity was 89.92%.
[0047] Example 7
[0048] The same as in Example 1, except that the non-lanthanum metal salt used in the catalyst preparation process was 0.121 g of ferric nitrate nonahydrate, and the other preparation steps remained unchanged. The yield of glycerol carbonate was 93.53%, and the selectivity was 99.94%.
[0049] Example 8
[0050] The same as in Example 1, except that the non-lanthanum metal salt used in the catalyst preparation process was 0.242 g of ferric nitrate nonahydrate, and the other preparation steps remained unchanged. The yield of glycerol carbonate was 89.75%, and the selectivity was 99.99%.
[0051] Example 9
[0052] The same as in Example 1, the amount of glycerol in the synthesis of glycerol carbonate was 1.73 g, the other steps remained unchanged, the yield of glycerol carbonate was 82.52%, and the selectivity was 96.84%.
[0053] Example 10
[0054] The same as in Example 1, the amount of glycerol in the synthesis process of glycerol carbonate was 2.59 g, the other steps remained unchanged, the yield of glycerol carbonate was 76.95%, and the selectivity was 95.68%.
[0055] Embodiment 11
[0056] The same as in Example 1, the amount of catalyst used in the synthesis process of glycerol carbonate was 0.035 g (the amount of catalyst used was 3% of the mass of glycerol), the other steps remained unchanged, the yield of glycerol carbonate was 74.64%, and the selectivity was 96.35%.
[0057] Example 12
[0058] The same as in Example 1, the amount of catalyst used in the synthesis process of glycerol carbonate was 0.081 g (the amount of catalyst used was 7% of the mass of glycerol), the other steps remained unchanged, the yield of glycerol carbonate was 84.72%, and the selectivity was 98.26%.
[0059] Embodiment 13
[0060] The same as in Example 1, the reaction temperature during the synthesis of glycerol carbonate was 120° C., the other steps remained unchanged, the yield of glycerol carbonate was 63.47%, and the selectivity was 92.69%.
[0061] Embodiment 14
[0062] The same as in Example 1, the reaction temperature during the synthesis of glycerol carbonate was 150° C., the other steps remained unchanged, the yield of glycerol carbonate was 85.24%, and the selectivity was 99.35%.
[0063] Embodiment 15
[0064] The same as in Example 1, the reaction pressure during the synthesis of glycerol carbonate was 5 kPa, the other steps remained unchanged, the yield of glycerol carbonate was 81.76%, and the selectivity was 96.83%.
[0065] Example 16
[0066] The same as in Example 1, the reaction pressure during the synthesis of glycerol carbonate was 10 kPa, the other steps remained unchanged, the yield of glycerol carbonate was 83.57%, and the selectivity was 97.34%.
[0067] Embodiment 17
[0068] The same as in Example 1, the reaction time in the synthesis process of glycerol carbonate was 3 h, the other steps remained unchanged, the yield of glycerol carbonate was 82.71%, and the selectivity was 96.91%.
[0069] Embodiment 18
[0070] The same as in Example 1, the reaction time in the synthesis process of glycerol carbonate was 6 h, the other steps remained unchanged, the yield of glycerol carbonate was 79.58%, and the selectivity was 95.39%.
[0071] Comparative Example 1
[0072] The same as Example 1, except that no non-lanthanum metal salt was added during the catalyst preparation process and other preparation steps remained unchanged, the yield of glycerol carbonate was 55.95% and the selectivity was 72.16%.
[0073] Comparative Example 2
[0074] The same as in Example 1, except that no ionic liquid was added during the catalyst preparation process and other preparation steps remained unchanged, the yield of glycerol carbonate was 63.47% and the selectivity was 79.44%.
[0075] Comparative Example 3
[0076] The same as in Example 1, the catalyst in the synthesis process of glycerol carbonate was 0.058 g of commercially available lanthanum oxide, and the other steps remained unchanged. The yield of glycerol carbonate was 42.92%, and the selectivity was 65.77%.
[0077] By comparing Examples 1 to 6, it can be seen that the iron-doped lanthanum oxide catalyst catalyzes the reaction of urea and glycerol to prepare glyceryl carbonate and exhibits the best catalytic performance, with a yield of 85.97% and a selectivity of 97.46% for glyceryl carbonate; by comparing Example 1 with Examples 8 to 9, it can be seen that the catalyst prepared when the molar ratio of the lanthanum element in lanthanum nitrate hexahydrate to the iron element in ferric nitrate nonahydrate is 1:0.1 has the best catalytic effect, with a yield of 93.53% and a selectivity of 99.94% for glyceryl carbonate; by comparing Example 1 with Examples 10 to 19, it can be seen that when urea and glycerol are mixed, the yield of glyceryl carbonate is 85.97% and the selectivity is 97.46%. When the glycerol molar ratio is 1.5:1, the catalyst dosage is 5% of the glycerol mass, the reaction temperature is 140°C, the reaction pressure is 7 kPa, and the reaction time is 4 hours, the iron-doped lanthanum oxide catalyst has the best activity in catalyzing the alcoholysis of urea to prepare glycerol carbonate; by comparing Example 7 with Examples 20 to 21, it can be seen that the metal-doped catalyst prepared by the present invention is still applicable to the reaction of urea with other alcohols; by comparing Examples 1 to 6 with Comparative Examples 1 to 3, it can be seen that the metal-doped lanthanum oxide catalyst prepared in the ionic liquid has significantly improved catalytic performance compared with the single lanthanum oxide catalyst.
Claims
1. A method for preparing a metal-doped lanthanum oxide catalyst and its application in catalyzing urea alcoholysis to synthesize glycerol carbonate, characterized in that: The catalyst preparation method is as follows: (1) weighing a certain ratio of lanthanum nitrate hexahydrate and non-lanthanum metal salt, adding them to anhydrous methanol, stirring them fully, waiting for them to dissolve, and then drying them in a vacuum drying oven at 60° C. to obtain a precursor; (2) Weigh an appropriate amount of anhydrous methanol and add it to the round-bottom flask containing the precursor, stir thoroughly until the precursor is completely dispersed; (3) Slowly add the ionic liquid into the round-bottom flask, and after it is dissolved, place it at 55°C for rotary evaporation. The obtained sample is centrifuged and washed in anhydrous ethanol, and finally transferred to a 60°C vacuum drying oven for drying. Wherein, the ionic liquid in step (3) is any one of imidazole salt, quaternary phosphonium salt and quaternary ammonium salt ionic liquid, and its structure is shown in the following formulas I, II and III: Wherein, in the ionic liquid structure, R1, R2, R3, and R4 are any one of C1-C8 alkyl groups; the anion X - It is any one of a halogen ion, a hydroxide ion, a tetrafluoroborate ion, a hexafluorophosphate ion, a carboxylate ion, and an imide ion.
2. The method for preparing the metal-doped lanthanum oxide catalyst according to claim 1, characterized in that: The metal element in the non-lanthanum metal salt in step (1) is any one of zinc, magnesium, aluminum, copper, iron, manganese, cobalt, nickel, calcium, zirconium and cerium; the anion in the non-lanthanum metal salt in step (1) is any one of halide ion, nitrate, sulfate, carbonate, acetate and phosphate.
3. The method for preparing the metal-doped lanthanum oxide catalyst according to claim 1, characterized in that: In the step (1), the molar ratio of the metal elements in the lanthanum nitrate hexahydrate and the non-lanthanum metal salt is 1:(0.01-0.5).
4. An application of the metal-doped lanthanum oxide catalyst according to claim 1 to catalyze the alcoholysis of urea to synthesize glycerol carbonate, characterized in that: The general reaction formula for synthesizing glycerol carbonate by catalyzing urea alcoholysis is as follows: The specific steps of synthesizing glyceryl carbonate are as follows: (1) Urea and glycerol in a certain molar ratio are added to a 25 mL round-bottom flask. The round-bottom flask is connected in sequence to a reflux condenser, an ammonia absorption device, and a vacuum pump, and is gradually heated in a constant temperature oil bath while being stirred continuously. (2) Then, an appropriate amount of the prepared metal-doped lanthanum oxide catalyst is weighed and added to the flask, and heating is continued while turning on the vacuum pump to maintain the system pressure. (3) After the reaction is completed, the product is cooled and the pressure in the system is restored to normal pressure; the catalyst is separated and recovered by centrifugation and washing, and the reaction product is quantitatively analyzed by gas chromatography.
5. The use of the metal-doped lanthanum oxide catalyst according to claim 4 to catalyze the alcoholysis of urea to synthesize glycerol carbonate, characterized in that: The molar ratio of urea to glycerol is (0.1-3):
1.
6. The use of the metal-doped lanthanum oxide catalyst according to claim 4 to catalyze the alcoholysis of urea to synthesize glycerol carbonate, characterized in that: The amount of the catalyst used is 1% to 10% of the mass of the glycerol.
7. The use of the metal-doped lanthanum oxide catalyst according to claim 4 to catalyze the alcoholysis of urea to synthesize glycerol carbonate, characterized in that: The alcoholysis reaction temperature is 100°C to 180°C.
8. The use of the metal-doped lanthanum oxide catalyst according to claim 4 to catalyze the alcoholysis of urea to synthesize glycerol carbonate, characterized in that: The alcoholysis reaction pressure is 5 to 50 kPa.
9. The use of the metal-doped lanthanum oxide catalyst according to claim 4 to catalyze the alcoholysis of urea to synthesize glycerol carbonate, characterized in that: The alcoholysis reaction time is 1 to 10 hours.
10. The use of the metal-doped lanthanum oxide catalyst according to claim 4 for catalyzing alcoholysis of urea to synthesize glycerol carbonate, characterized in that: Glycerol carbonate was prepared by using urea and glycerol in a molar ratio of 1.5:1 as raw materials at a reaction temperature of 140° C. and a reaction pressure of 7 kPa for 4 hours.
Citation Information
Patent Citations
Catalyst for producing glycerol carbonate from glycerin, method for producing same, and method for producing glycerin carbonate using the same
CN103357394B
A method for synthesizing glycerol carbonate
CN114957009B
Catalyst for synthesizing glycerol carbonate as well as preparation method and application of catalyst
CN117339619A